Dari Alam untuk Edukasi: Keberhasilan Bedengan Serorejo dalam Merintis Eduwisata Jelajah Sungai dan Agroforestri - Arisoesilaningsih, Endang; Retnaningdyah, Catur; Sianturi, Riswan (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
Bedengan Campground (BPB) Selorejo, Malang Regency, offers beautiful landscapes and is a priority for rural development with a mission of conserving nature, culture, and local wisdom. Until now, there have been no tourist services other than camping, while the potential of local nature needs to be developed for diversification and productivity of services. This initiative aims to assist managers in enhancing their guiding skills and launching new nature-based educational tourism programs to enrich outdoor classes, utilizing local resources, specifically: a) river biodiversity exploration for water quality monitoring (River Adventure Tour) and b) agroforestry exploration for watershed conservation (Agroforestry Adventure Tour). The program was initiated by inviting 20 high school, junior high school, and elementary school students accompanied by biology teachers, curriculum coordinators, or counselors. The eco-tourism program took place in three phases in September, October, and November 2024, from 8:30 AM to 4:00 PM WIB, with a half-day session for elementary school students. Leaflets were distributed in soft copy format prior to the tour. The managers underwent training in guiding skills. Subsequently, the BPB managers were involved in the implementation of the educational tour at three schools, starting as observers and eventually becoming guides. The results of the development and initiation of eduwisata show that the river exploration and agroforestry exploration tour packages can be carried out smoothly, with students showing great enthusiasm, satisfying all participants, and achieving the set recreational and learning targets. All teachers expressed appreciation and rated both eduwisata programs as highly engaging, relevant, with a clear mission, and enjoyable for enhancing students' knowledge and skills. Tour guides successfully improved their skills and tested this educational tourism program while continuously improving time management, governance, and organization.